Indications of future performance of native and non-native adult oysters under acidification and warming. (November 2018) - Lemasson, Anaëlle J.; Hall-Spencer, Jason M.; Fletcher, Stephen; Provstgaard-Morys, Samuel; Knights, Antony M.
Abstract: Globally, non-native species (NNS) have been introduced and now often entirely replace native species in captive aquaculture; in part, a result of a perceived greater resilience of NSS to climate change and disease. Here, the effects of ocean acidification and warming on metabolic rate, feeding rate, and somatic growth was assessed using two co-occurring species of oysters – the introduced Pacific oyster Magallana gigas (formerly Crassostrea gigas ), and native flat oyster Ostrea edulis . Biological responses to increased temperature and p CO2 combinations were tested, the effects differing between species. Metabolic rates and energetic demands of both species were increased by warming but not by elevated p CO2 . While acidification and warming did not affect the clearance rate of O. edulis, M. gigas displayed a 40% decrease at 750 ppm p CO2 . Similarly, the condition index of O. edulis was unaffected, but that of M. gigas was negatively impacted by warming, likely due to increased energetic demands that were not compensated for by increased feeding. These findings suggest differing stress from anthropogenic CO2 emissions between species and contrary to expectations, this was higher in introduced M. gigas than in the native O. edulis . If these laboratory findings hold true for populations in the wild, then continued CO2 emissions can be expected to adversely affect the functioning and structure of M. gigas populations with significant ecological and economic repercussions, especially for aquaculture. Our findings strengthen arguments in favour of investment in O. edulis restoration in UK waters. Highlights: Acidification and warming negatively impacted the physiology of Magallana gigas . Ostrea edulis appeared unaffected by the treatment conditions. Efforts to promote the restoration of native O. edulis beds should be pursued. Efforts to eradicate M. gigas populations may need to be reconsidered.